Воведување на е-бизнис за зголемување на конкурентноста на малите и средните претпријатија во Република Македонија - Сандев, Зоран (Економски факултет, УКИМ, Скопје, 2015)
Strategy of development of electronicworking process can be very useful for companies providing competitive advantages. Strategy is the basic formula for how to set up the business to be competitive, that goals should have and which plans and policies are needed to achieve these goals. The strategy of the organization sets fundamental questions about the current position of the company. In the phase of e-business, organization examining themselves and their environment. The main activities include an adjustment of the mission of the organization and its goals checking the strength and weaknesses of the organization, accessing to environmental factors affecting e-business and analysis of competition. For the purposes of e-business planning, this includes examining the potential benefits that the Internet and other technologies can engage in business. Subject matter of this doctoral dissertation is an analysis of e-business in enterprises and increase their competitiveness. This means the way of implementation of e-business enterprises in a group of independent factors affecting competitiveness. To determine which factors in the implementation of e-business in SMEs increased competitiveness will do research that will get detailed information about the factors of success before starting a quantitative research. In the theoretical part of the paper and the development of a model for the impact of e-business on competitiveness not accurately defined models, but the models which themselves include factors that have the greatest impact on competitiveness but is associated with the implementation of e-business based on this is selected Conner model, which placed the factors that affect competition on three levels and factors which include the introduction of e-business.
Establishing e-business to increase competitiveness on small and medium firm in the Republic of Macedonia
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Сашо Јосимовски.
Keywords: competitiveness, e-business, e-business models, key factors for competitiveness